Update on the Financing of the Fund's Concessional Assistance and Proposed Amendments to the PRGT Instrument. (Policy Papers; Policy Paper ;, 2014)
New commitments under PRGT-supported programs amounted to SDR 0.15 billion in 2013, while disbursements on existing arrangements amounted to about SDR 0.8 billion. However, this lower demand is expected to be temporary. New commitments are projected to rebound to about SDR 1.5 billion in 2014, similar to the level observed in 2012. These projections are subject to considerable uncertainty regarding progress on ongoing program negotiations.